Entrance surface dose from pediatric diagonostic x-ray examinations in a developing world setting: are we 'ALARA principle' compliant? (2013)
Background: Rediation protection in paediatric radiology requires special attention than in adult because children are more sensitive to radiation and at higher risk. This risk is explained by the longer life expectancy in children which allows for harmful effect of radiation to manifest and thier developing organs and tissues being more sensitive to radiation. Hence, the need for determination of appropraite radiation dose for paediatric patients. Aims:to estimate entrance skin dose (ESD) recieved by paediatric patients during diagnostic x-ray examinations. Material and Methods: A total of 253 paediatric patients undergoing various x-rays examinations between June 2011 and December, 2012. In a teaching hospital in the south west Nigeria were considered in this study. This hospital has no dedicated x-ray unit for paediatric radiology. The ESD recieved during x-ray examination was calculated using mathematical formular that incorporated the use of x-ray beam output and exposure parameters selected for examination. Correlation coefficient (r) analysis was used to test the relationship between ESD, patient size (age and weight) and exposure parameters(KVp, mAs). Results: The ESD and ED recieved by paediatric patients from all the x-ray examinations considered in this study ranged from 10.29+3.80-880.04+89.44 µGy 0.01 level of significant showed that there is a correlation between patient does and exposure factors but there is no correlation between ESD, age and weight of patients. Conclusion: The ESD recieved by paediatric patients is higher that the internationally recommended reference dose. This is attributed to lack of dedicated x-ray unit and personnel for paediatric radiology.